E-governance: a medium for moving towards good governance - Balaram; Adhikari, Bibhar (2009)
Good governance and e-governance are interrelated with one another. The process of e-governance is clear, simple and inexpensive. It provides not only easier access to delivery of services but also greater accountability and transparency in the operations. The present article is intended to prove this as a fact by discussing issues like (a) benefit of digitizing the governance procedures (b) scope of e-governance (c) maturity models for mapping the levels of e-governance which is analogous with the building of a house. - Reproduced.
Keywords: Good governance; E governance